Patterns of Delirium in a Pediatric Intensive Care Unit and Associations With Noise Pollution. (July 2022) - Weatherhead, Jeffrey R.; Niedner, Matthew; Dahmer, Mary K.; Malas, Nasuh; Owens, Toni; Kawai, Yu
Objective: Delirium is a common problem in the Pediatric Intensive Care Unit (PICU) and is associated with increased length of stay, cost and mortality. This study evaluated the relationship between noise pollution and delirium risk.Design: This is a Quality Improvement (QI) initiative at an academic PICU. Sound levels were monitored and patients were screened for delirium using the Cornell Assessment of Pediatric Delirium (CAPD).Setting PICUPatients: All PICU patientsInterventions: NoneMeasurements and Main Results: Over the 83-week study period (2015-2017), the median [IQR] CAPD score was 8 [3 to 14]. Nursing compliance with the CAPD was 72.2%. The proportion of patients screening positive for delirium (CAPD ≥ 9) was 45.9%. A total of 329 711 hly decibel (dB) measurements were collected and reported. Occupied rooms were louder than unoccupied rooms (51.8 [51.6-51.9] dB vs. 49.8 [49.7-49.9] dB, respectively, p  < 0.001). Days (10 AM to 4 PM) were louder than nights (11 PM to 5 AM) (52.8 [52.7-53.0] dB vs. 50.7 [49.9-51.5] dB, respectively p  < 0.001) in occupied rooms. Winter (Nov-Feb) months were louder than summer (May-Aug) months (52.0 [51.8-52.3] dB vs. 51.5 [51.3-51.7] dB, respectively, p < 0.002) in occupied rooms. Median weekly nighttime noise levels and CAPD scores demonstrated a correlation coefficient of 0.6 ( p  < 0.001). Median weekly risk of mortality (ROM) and CAPD scores demonstrated a correlation coefficient of 0.15 ( p  < 0.01).Conclusions: Significant noise pollution exists in the PICU with a moderate correlation between nighttime noise levels and CAPD scores. This could potentially implicate noise pollution as a risk factor for the development of delirium.